Attomolar detection of extracellular microRNAs released from living prostate cancer cells by a plasmonic nanowire interstice sensor. Issue 44 (2nd November 2017) - Yang, Siyeong; Kim, Hongki; Lee, Kyung Jin; Hwang, Seul Gee; Lim, Eun-Kyung; Jung, Juyeon; Lee, Tae Jae; Park, Hee-Sung; Kang, Taejoon; Kim, Bongsoo
Abstract : Extracellular miR141 and miR375 released from living human prostate cancer cell lines were clearly verified by using an extremely sensitive and specific PNI sensor. Abstract : Prostate cancer (PC) is the second leading cause of cancer death for men worldwide. The serum prostate-specific antigen level test has been widely used to screen for PC. This method, however, exhibits a high false-positive rate, leading to over-diagnosis and over-treatment of PC patients. Extracellular microRNAs (miRNAs) recently provided valuable information including the site and the status of the cancers and thus emerged as new biomarkers for several cancers. Among them, miR141 and miR375 are the most pronounced biomarkers for the diagnosis of high-risk PC. Herein, we report an attomolar detection of miR141 and miR375 released from living PC cells by using a plasmonic nanowire interstice (PNI) sensor. This sensor showed a very low detection limit of 100 aM as well as a wide dynamic range from 100 aM to 100 pM for all target miRNAs. In addition, the PNI sensor could discriminate perfectly the diverse single-base mismatches in the miRNAs. More importantly, the PNI sensor successfully detected the extracellular miR141 and miR375 released from living PC cell lines (LNCaP and PC-3), proving the diagnostic ability of the sensor for PC. We anticipate that the present PNI sensor can hold great promise for the precise diagnosis and prognosis of various cancer patients as well as PC patients.